A formação inicial de professores de geografia no PIBID/UNIOESTE Campus de Marechal Cândido Rondon-PR (2011-2015) - Woitowicz, Eliete (2016)
This this dissertation was to analyze the performances of the Institutional Program Geography Subproject Initiation Grant to Teaching (PIBID), the State University of Western Paraná (UNIOESTE), campus Marechal Cândido Rondon (MCR), entitled "The teaching of geography: from theory to practice", in the period from 2011 to 2015, before the improvement, enhancement and qualification of initial teacher training . In addition, it sought to understand the historical and political context in which the PIBID arose in order to contextualize the public educational policies that bolster. The presentation of this scenario enables the understanding of reforms in teacher education policies and at the same time, the understanding of how PIBID was established as public policy of the State. He tried to work the concept of initial teacher training in order to correlate it to the performances of PIBID of Geography UNIOESTE/MCR. Favorable condition to show that the Subproject's actions are consistent with the purposes of the program, and assign quality training of Geography teachers. We sought to identify the works, research and activities of the pibidianos contribute indeed to initial teacher education, relating the practices developed in the Sub-project with the discussion of the minister Geography classes more attractive and meaningful. Therefore, in addition to the relevant literature to the field of research, we used qualitative analysis through the case study technique, with the participation of twelve (12) initiation scholarship to teaching and 03 (three) supervising teachers (fellows and volunteers) Geography Subproject, through semi-structured interview of development with open questions, which were audio-recorded and transcribed. Developed open questionnaire with two classes of 7th grade of elementary school - a total of 49 (forty nine) students - who participate in the activities of Geography PIBID for over a year and six months in two schools public of the city of MCR that integrate Subproject under review. It was found that the Subproject actions PIBID of Geography UNIOESTE/MCR is crucial to assist and improve initial teacher training, especially in relation to the learning of the teaching profession, and improve the quality of geography teaching in schools and University. However, it was also possible to see some difficulties posed to the program, which caused political instability to PIBID. Thus, through this study, we present the opportunities and challenges facing the Subproject above before the initial training of Geography teachers. It is expected that the results will contribute to the strengthening and continuity of PIBID, in order to expand the program to a larger number of undergraduate students in Brazil and, simultaneously, in public schools of Basic Education. It also seeks to encourage changes in how the Degree in Geography (UNIOESTE/MCR) is seen especially in relation to the attitude of some undergraduates and teachers who do not sympathize with teaching.